GDPR AND CHALLENGES OF PERSONAL DATA PROTECTION - Žaklina ,; Vicentijevic, Kosana (The European Journal of Applied Economics, 2022)
The paper discusses the challenges of implementing GDPR regulation in the EU and theRepublic of Serbia. The regulations governing the issue of personal data protection areoutlined. Emphasis is placed on reconciling this issue in the Republic of Serbia with EUlegislation. The aim of this paper is to look at GDPR regulations from several aspects of thebusiness of taxpayers. It is necessary to include all segments of the business entity in theimplementation of this regulation, as well as bodies at the national level. It is necessary toadopt by-laws in order to fully implement the Law on Personal Data Protection in theRepublic of Serbia.
Keywords: GDPR, personal data, compliance, data protection